The Rubidge Collection of fossil Karroo vertebrates - Haughton, S. H. (Bernard Price Institute for Palaeontological Research, 1965)
Wherever palaeontologists interested in fossils from the strata of the Karroo system discuss the systematics and evolutionary importance of Permian and Triassic vertebrates they perforce have to consider the facts that have been revealed by studies of the hundreds of specimens forming what is known as the "Rubidge Collection".
Main article
Keywords: Rubidge Collection; Karroo; South Africa